Effect of paclitaxel-cisplatin chemotherapy towards hemoglobin, platelet, and leukocyte levels in epithelial ovarian cancer patients - Rini Noviyani, P. A. Indrayathi, I. N. G Budiana, Rasmaya Niruri, K. Tunas, N. M. Dhatu Dewi Adnyani (Journal of Applied Pharmaceutical Science, 2019)
Paclitaxel-cisplatin combination chemotherapy as first-line treatment of epithelial ovarian cancer (EOC) is known to cause myelosuppression that leads to decreased hemoglobin, platelet and leukocyte levels. This study aims to evaluate the side effect of paclitaxel-cisplatin chemotherapy in EOC patients with hematologic status at Sanglah General Hospital, Denpasar. Observational retrospective research was conducted from February to May 2018. Samples were EOC patients who underwent six cycles of paclitaxel-cisplatin chemotherapy at Sanglah General Hospital, Bali- Indonesia from January 2015 to May 2018. Side effects of chemotherapy were seen from hemoglobin, platelet, and leukocyte data before and after six cycles of chemotherapy. Hematologic data were analyzed and compared using Paired T-test with a level of confidence of 95% using the STATA version 14 software. Mean value of three hematologic parameters decreased after six cycles, including hemoglobin levels were 12.05–10.69 g/dl (p-value = 0.282); platelet levels were 378.5–326.9 g/dl (p-value = 0.569) and leukocyte levels were 11.32–8.28 g/dl (p-value = 0.517). There were differences of hemoglobin, platelet, and leukocyte levels before the first and after the sixth cycle of chemotherapy. Low side effects of paclitaxel-cisplatin were observed in this study (Anemia grade 1).
Keywords: Chemotherapy, paclitaxel-cisplatin, epithelial ovarian cancer, hemoglobin, platelet, leukocyte.